Population pharmacokinetic analysis to recommend the optimal dose of udenafil in patients with mild and moderate hepatic impairment - Kim, Anhye (Br J Clin Pharmacol, 2016)
AIMS: The aim of this study was to develop a population pharmacokinetic (PK) model of udenafil and its active metabolite, DA‐8164, in healthy subjects and patients with hepatic impairment (HI) and to estimate the optimal dosing recommendations for patients with HI. METHODS: An open label, three parallel group, age and weight matched control study was conducted in 18 volunteers, six healthy subjects (n = 6) and patients with mild (Child–Pugh class A, n = 6) and moderate HI (Child–Pugh class B, n = 6). Serial blood samples were collected for up to 72 h after a single administration of udenafil 100 mg. A population PK model was developed using non‐linear mixed effects modelling (nonmem, ver. 7.2). The simulated data from the final PK model and original data of healthy subjects were compared to identify the optimal dose for patients with HI. RESULTS: A two compartment model for both udenafil and DA‐8164 best described the data. Prothrombin time on metabolic clearance of udenafil to DA‐8164 was included in the final model as a covariate. Compared with the AUC(0,t (last)) value after administration of udenafil 100 mg to healthy subjects, the geometric mean ratios (95% confidence interval) after 100 mg and 75 mg udenafil administration were 1.21 (1.10, 1.32) and 0.74 (0.67, 0.81) in patients with mild HI, respectively. Meanwhile, those were 1.55 (1.43, 1.67) and 1.02 (0.92, 1.12) in patients with moderate HI, respectively. CONCLUSIONS: This study suggests that the recommended doses of udenafil are 100 mg and 75 mg in patients with mild and moderate HI, respectively.